A Descriptive-Correlational Study on Personality Traits and Entrepreneurial Intentions of Senior High School Learners - Clarete, Princess Maejoy D.; Mondejar, Marlou Antonio D.; Quimba, Nel Rose L.; Gaygay, Carlos, Jr. (Future Science / FSH-PH Publications, 2023)
Personality traits play a crucial role in shaping theories related to entrepreneurial processes, particularly in terms of entrepreneurial intentions. This study aimed to assess the levels of personality traits and entrepreneurial intentions among Grade 12 students in Science, Technology, Engineering, and Mathematics (STEM) and Humanities and Social Sciences (HUMSS) senior high school programs, as well as to explore their significant relationships. Employing a descriptive correlational research design, the study involved 211 Grade 12 STEM and HUMSS students selected through stratified random sampling. Conducted via online forms, the results indicated high levels of openness to experience, conscientiousness, extraversion, agreeableness, and neuroticism, alongside elevated entrepreneurial intentions. Additionally, Spearman’s correlation revealed significant relationships between openness to experience, conscientiousness, extraversion, and agreeableness with entrepreneurial intentions. However, no significant relationship was found between neuroticism and entrepreneurial intentions. Importantly, the study identified relationships between personality traits and entrepreneurial intentions among Grade 12 STEM and HUMSS senior high school learners.